74 Patient-oriented research priorities for pediatric hospital care in Canada: a James Lind Alliance Priority Setting Partnership. (21st October 2022) - Gill, Peter; Bayliss, P; Breen-Reid, Karen; Buchanan, Francine; De Castris-Garcia, Kim; Green, Mairead; Frappier, Shelley; Quinlan, Michelle; Wong, Noel; Cowan, Katherine; Mahant, Sanjay; ,
Abstract: Background: The largest population of paediatric patients cared for in hospital are those with medical conditions managed in general paediatric inpatient units (GPIUs). Despite the large burden, there is a lack of high-quality research focused on the care of children and youth admitted to GPIUs. The Canadian Paediatric Inpatient Research Network (PIRN) was launched in 2019 to generate evidence to improve the care and outcomes for hospitalized children in GPIUs. To help establish a future research agenda, PIRN brought together clinicians, youth, patients and caregivers to identify important clinical management questions about the care of children in hospital. Objectives: To conduct a research priority setting study to identify the most important unanswered clinical management research questions about paediatric hospital care in GPIUs that are important to patients, caregivers, and clinicians. Design/Methods: Established James Lind Alliance Priority Setting Partnership methodology was utilized for this project, which was overseen by a Steering Group composed of patient partners, (youth, parents of patients) and clinicians (nurses, and paediatricians) (n=10), facilitated by a JLA Adviser. In phase 1, an online REDCap survey was administered to collect unanswered research questions regarding paediatric hospital care via 3 open-ended questions. Responses from the phase 1 survey went through a detailed evidence checking process. Subsequently, unanswered research questions were brought forward to a phase 2 interim prioritization online REDCap survey. A final list of top 10 unanswered research questions pertaining to paediatric hospital care was established at the final priority setting workshop. Results: The phase 1 survey was completed by 188 participants and generated 495 unanswered research questions and comments, of which 58 were deemed out of scope. The remaining 437 responses were grouped into themes (e.g., hospital policy, communication, shared-decision making, health service delivery and health service management), and then refined to 75 unanswered research questions. Of these 75, 4 questions had sufficient evidence, and 21 were submitted by only one respondent. Fifty unanswered research questions were included in the phase 2 survey, which was completed by 201 participants. The top 16 questions – the top 10 from both patient partners (youth, parents of patients) and clinicians respectively – were presented at the final priority setting workshop and the top 10 questions were prioritized (Table 1). The top 10 questions focus on the care of special inpatient populations (e.g. children with medical complexity), communication, shared-decision making, support strategies, mental health supports, shortening length of stay, and supporting Indigenous patients, parents and families. Conclusion: The top 10 unanswered questions on paediatric hospital care will help guide future research. PIRN will use these prioritized questions to generate scientific knowledge to improve the outcomes of hospitalized children and youth in GPIUs through the conduct of patient-oriented research.